Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized for You

we will pick new questions that match your level based on your Timer History

Track Your Progress

every week, we’ll send you an estimated GMAT score based on your performance

Practice Pays

we will pick new questions that match your level based on your Timer History

Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.

Thank you for using the timer!
We noticed you are actually not timing your practice. Click the START button first next time you use the timer.
There are many benefits to timing your practice, including:

Re: Sequence is making me go bonkers!! [#permalink]
15 Aug 2011, 03:27

"for starters u could use the substitution technique where n =2 ==> sn = 3

then s(2n) = s(4) = 10 only D satisfies"

Can you explain how you would get s(n) = 3 if n is 2. disregarding the format of the sequence, if n is 2, the sum of the sequence should be at least 12 (10...+ 2).

its clearly much quicker than doing it mathematically! but I did go the math route, and my only falter compared to your calculation is that I cannot see how you've got rid of the division by 2 in the S(n) calculations.

Re: Sequence is making me go bonkers!! [#permalink]
15 Aug 2011, 03:46

1

This post received KUDOS

DeeptiM wrote:

If S(n) is the sum of sequence 1, 2, 3, 4, ...n, in terms of n and S(n), S(2n)=? (A) 2*S(n) (B) n*S(n) (C) 2n*S(n) (D) 2S(n)+n^2 (E) S(n)+2n^2

Pls help with the easiest explanation possible..thnx

Let's see the pattern:

For n=5, the sequence will be {1,2,3,4,5} S(n)=S(5)=1+2+3+4+5

2n=2*5=10, the sequence will be {1,2,3,4,5,6,7,8,9,10} S(2n)=S(10)=1+2+3+4+5+6+7+8+9+10=1+2+3+4+5+(1+5)+(2+5)+(3+5)+(4+5)+(5+5) (1+2+3+4+5)+(1+2+3+4+5)+(5+5+5+5+5) S(5)+S(5)+5*5=S(5)+S(5)+5^2=2S(5)+5^2

Since, n=5 2S(5)+5^2=2S(n)+n^2

In general terms, S(n)=1+2+3+4,...+n S(2n)=1+2+3+4,...+n+(1+n)+(2+n)+(3+n)+(4+n),...+(n+n) S(2n)=(1+2+3+4+...+n)+(1+2+3+4+...n)+(n+n+...n-times) S(2n)=S(n)+S(n)+n^2 S(2n)=2S(n)+n^2

Re: Sequence is making me go bonkers!! [#permalink]
15 Aug 2011, 03:59

1

This post received KUDOS

meshell wrote:

"for starters u could use the substitution technique where n =2 ==> sn = 3

then s(2n) = s(4) = 10 only D satisfies"

Can you explain how you would get s(n) = 3 if n is 2. disregarding the format of the sequence, if n is 2, the sum of the sequence should be at least 12 (10...+ 2).

its clearly much quicker than doing it mathematically! but I did go the math route, and my only falter compared to your calculation is that I cannot see how you've got rid of the division by 2 in the S(n) calculations.

"Therefore Sn = n(1+ n)/2 or n+n^2 = 2Sn -- (1)"

Shouldn't n(1 + n) / 2 become n + n^2 / 2?

Michelle, the series is 1,2,3,4,.... and Sn is the sum of the series until n terms .. so the sum of the series for 2 terms or s(2) = 1+2 = 3

and s(4) = 1+2+3+4 = 10

i hope this helps explain your concern on "disregarding the format of the sequence, if n is 2, the sum of the sequence should be at least 12 (10...+ 2). " if you still have questions, i'll be happy to help.

on the mathematical formula yes sn = [n(1+n)] / 2 and is therefore indeed sn = [n + n^2] / 2 but to avoid confusion, i have pulled the 2 to the other side making it 2* Sn = [n + n^2]

Re: Sequence is making me go bonkers!! [#permalink]
15 Aug 2011, 04:02

fluke wrote:

DeeptiM wrote:

If S(n) is the sum of sequence 1, 2, 3, 4, ...n, in terms of n and S(n), S(2n)=? (A) 2*S(n) (B) n*S(n) (C) 2n*S(n) (D) 2S(n)+n^2 (E) S(n)+2n^2

Pls help with the easiest explanation possible..thnx

Let's see the pattern:

For n=5, the sequence will be {1,2,3,4,5} S(n)=S(5)=1+2+3+4+5

2n=2*5=10, the sequence will be {1,2,3,4,5,6,7,8,9,10} S(2n)=S(10)=1+2+3+4+5+6+7+8+9+10=1+2+3+4+5+(1+5)+(2+5)+(3+5)+(4+5)+(5+5) (1+2+3+4+5)+(1+2+3+4+5)+(5+5+5+5+5) S(5)+S(5)+5*5=S(5)+S(5)+5^2=2S(5)+5^2

Since, n=5 2S(5)+5^2=2S(n)+n^2

In general terms, S(n)=1+2+3+4,...+n S(2n)=1+2+3+4,...+n+(1+n)+(2+n)+(3+n)+(4+n),...+(n+n) S(2n)=(1+2+3+4+...+n)+(1+2+3+4+...n)+(n+n+...n-times) S(2n)=S(n)+S(n)+n^2 S(2n)=2S(n)+n^2

Ans: "D"

Thanks Fluke for saving my back on so many occasions kudos to u!!

Piyush K ----------------------- Our greatest weakness lies in giving up. The most certain way to succeed is to try just one more time. ― Thomas A. Edison Don't forget to press--> Kudos My Articles: 1. WOULD: when to use?| 2. All GMATPrep RCs (New) Tip: Before exam a week earlier don't forget to exhaust all gmatprep problems specially for "sentence correction".

gmatclubot

If S(n) is the sum of sequence 1, 2, 3, 4, ...n, in terms of
[#permalink]
07 Sep 2014, 23:21